Spectroscopic Investigations of the Oxidative Polymerization of Hydroquinone in the Presence of Hexavalent Chromium. (22nd August 2016) - Cheng, Ching-Yun; Chan, Ya-Ting; Tzou, Yu-Min; Chen, Kai-Yue; Liu, Yu-Ting
Abstract : Polyphenol polymerization receives much scientific attentions because it is an important reaction of humification processes. Through an oxidative polymerization reaction (OPR), hydroquinone (H2 Q), a naturally occurring compound, has been found to be a vital precursor of humic substances in soils. Chromate (Cr(VI)), a strong oxidant, is widely distributed in the environment due to the inappropriate disposal of Cr-containing wastes. The OPR of H2 Q in the presence of Cr(VI) may occur naturally. In the study, it was found that 400 mg L −1 H2 Q could be polymerized at pH 3.0 with 105 mg L −1 Cr(VI). The results of FT-IR revealed the presence of both hydroquinone and benzoquinone nuclei in the polymer. The spectra of X-ray absorption near edge structure (XANES) demonstrated a decrease in Cr(VI) content during the OPR of H2 Q. Based on the results of linear combination fitting (LCF) for the spectra of XANES, the proportions of Cr species in the precipitates mainly consisted of Cr(OH)3, and Cr-carboxylate contents increased gradually from 15.3 to 25.5% over the reaction time. After acidizing the supernatants at pH 1.0 for 1 d, Cr(III)-HA dominated Cr(III) species. This suggested that humic-like substances were formed during OPR of H2 Q, possibly through the formation of Cr(III)-organic complex.